Pretreatment with Low-Dose Esketamine for Reduction of Propofol Injection Pain: A Randomized Controlled Trial. (2nd August 2022) - Fu, Danyun; Wang, Dingding; Li, Wenxian; Han, Yuan; Jia, Jie
Abstract : Background . Propofol-induced injection pain is a common adverse effect during the induction of general anesthesia. The purpose of this study is to investigate the effect of low-dose esketamine in preventing propofol injection pain. Methods . In this double-blind, randomized, controlled trial, patients scheduled for elective ear surgery under general anesthesia received either normal saline (NS), or 40 mg lidocaine, or 0.15 mg/kg esketamine 30 seconds before manual injection of propofol. The primary outcome of this study was the incidence of propofol injection pain. The secondary outcomes included injection pain score, vital signs, total dosage of vasoactive drugs used within 5 minutes after induction, and adverse events related to drugs. Results . A total of 105 patients were included. Compared with the NS group (67%), pretreatment with esketamine and lidocaine significantly reduced the incidence of injection pain to 29% and 33%, respectively (both P < 0.05 ); however, no significant difference was found between the esketamine and lidocaine groups. The median of injection pain score was significantly lower in the esketamine and lidocaine groups (both median (interquartile range) = 0 (0–1)) than that in the NS group (1 (0–2); P < 0.05 ). In addition, compared with the NS and lidocaine groups, preinjection esketamine provided more stable hemodynamic parameters within 5 minutes after induction (P < 0.05 ). No statistical difference was found in adverse events among the three groups. Conclusions . Pretreatment with a low-dose esketamine can not only reduce the incidence of propofol injection pain but also provide a more stable circulation in patients after anesthesia induction. This convenient, well-tolerated, and economic treatment appears as an option to be routinely applied in clinic practice. Clinical Trial Registration. This trial is registered with https://www.chictr.org.cn/showproj.aspx?proj=136690 (the number for the trial registration isChiCTR2100052742 ).